Constructing Long-Only Multifactor Strategies: Portfolio Blending vs. Signal Blending. Issue 3 (1st July 2018) - Ghayur, Khalid; Heaney, Ronan; Platt, Stephen
Abstract : Long-only multifactor strategies may be constructed by combining individual-factor portfolios (portfolio blending) or by combining individual-factor signals into a composite signal to construct the portfolio (signal blending). To compare these two approaches, we present a framework for building exposure-matched portfolios. In empirical tests on global equity markets, we find that, generally, portfolio blending generates higher information ratios for low-to-moderate levels of tracking error. At high levels of tracking error, signal blending delivers better risk-adjusted performance. These results generally hold for various factor combinations, and they have important practical implications for investors considering the implementation of multifactor smart-beta strategies. Abstract : A practitioner's perspective on this article is provided in the In Practice piece "Comparing Portfolio Blending and Signal Blending when Constructing Multifactor Portfolios " by Keyur Patel, online 23 July 2018. Disclosure: The authors work at Goldman Sachs Asset Management, which offers strategies that use both the portfolio-blending and signal-blending approaches to factor investing. Additional disclosures can be found at the end of this article. Editor's Note Submitted 30 March 2017 Accepted 16 March 2018 by Stephen J. Brown This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in the acknowledgments. Markus Leippold was one of the reviewers for this article. Disclosure: The views and opinions expressed herein are those of the authors. The backtests and analysis described are provided for educational purposes in reliance on past market data with the benefit of hindsight and do not reflect actual results. If any assumptions used do not prove to be true, results may vary substantially. Our research does not take into account specific investment objectives or investor guidelines or restrictions. Investors must also consider suitability, liquidity needs, and investment objectives when determining appropriate asset allocation.